The state as cultural practice - Bevir, Mark.; Rhodes, R. A. W. (Oxford Oxford University Press, 2010)
'The State as Cultural Practice' offers an original theory of the state. In place of the institutional state, Bevir and Rhodes argue for 'the stateless state', or for a focus on the contingent beliefs and practices of individuals. In short, they put the people back into the study of the state.
Electronic reproduction.
Keywords: State, The; State, The -- Social aspects; Electronic books